MUCOADHESIVE CHITOSAN MICROSPHERES OF GEFITINIB - Soni, Mohnish; Majumdar, Arti; Malviya, Neelesh (International Journal of Current Pharmaceutical Research, 2018)
Objective: Gefitinib, Epidermal Growth Factor-Tyrosine Kinase Inhibitor (EGFR-TKI); has promisingly shown activity against Non-Small-Scale Lung Cancer. Currently, the formulations of this drug available are in Tablets, Capsules and liposomal suspensions taken by the oral route. These have certain disadvantages in gastrointestinal disorders like irritation of GI mucosal layer, bleeding, non-patient compliance and low bioavailability due to low aqueous solubility and thus low bioavailability. The purpose of this study was to formulate and evaluate Chitosan-based Microparticles of Gefitinib for maintaining the therapeutic index and limits its side effects. Methods: Chitosan microspheres cross-linked with glutaraldehyde were prepared by solvent evaporation technique which is then analyzed for its particle size, encapsulation efficiency, swelling index. Results: The release rate of the drug can be increased by using chitosan-based carrier system which will enhance its bioavailability. By this work, the anticancer activity of Gefitinib in non-small-scale lung cancer will be successfully determined. Conclusion: It has been concluded that microspheres can be prepared by solvent evaporation technique by varying the concentration of chitosan and tween-20. Chitosan used in this work is of 85 % degree of deacetylation, 25 % solution of Gluteraldehyde suitable for the formulation of these microspheres. Optimized temperature was selected as 65 Â°C, and the rotation speed was taken as 1200 rpm. Finally, the objectives planned for this research work was performed and evaluated and shown promising results as the dosing frequency is reduced and maximize for 3 d rather than once in a day as per the current formulation available in the market now with a low dosage regimen of 100 mg of dosage strength, administer by pulmonary route. Microparticulate drug delivery system from microspheres is able to deliver the drug in a sustained release manner for the long period of time successfully.